Bank ownership, lending relationships and capital structure: Evidence from Spain - Carlos Fernández Méndez; Víctor Manuel González Méndez (BRQ Business Research Quarterly, 2019)
This paper analyses the influence of bank ownership and lending on capital structure for a sample of listed and unlisted Spanish firms in the period 2005-2012. The results suggest that bank ownership allows banks to obtain better information and reduce the agency costs of debt, as it has a positive relationship with the maturity of debt and a negative relationship with the cost of debt. These results are consistent with the predominance of the monitoring effect in bank ownership over the expropriation effect. The role of banks as shareholders and lenders also contributes to reduce agency cost of debt, as it reduces debt cost.
Keywords: G32; 650; Bank lending; Bank ownership; Debt; Debt cost; Debt maturity